Using the hofstede-gray framework to argue normatively for an extension of Islamic corporate reports / Maliah Sulaiman and Roger Willett - Sulaiman, Maliah; Willett, Roger (Faculty of Accountancy & Accounting Research Institute (ARI), 2003)
Baydoun and Willett (2000) suggest that the inclusion of the current value balance sheet and the value added statement in Islamic corporate reporting may be considered as satisfying the concepts of full disclosure and social accountability in Islam. Using the Hofstede-Gray framework, this paper provides theoretical support for Baydoun and Willett's (2000) Islamic corporate reporting model and also extends the model to include the reporting of the social and environmental aspects of the enterprise. What constitutes social reporting from Islam's perspective is developed from the Shari'a and the list of economic, social and environmental indicators proposed by the Global Reporting Initiative.